2018
DOI: 10.3390/soilsystems2040057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Fertility under Different Land-Use Systems in Dhading District of Nepal

Abstract: Unscientific land use and cropping techniques have led high soil erosion and degradation of soil quality in the mid-hills of Nepal. To understand the effects of land use systems for selected soil chemical properties in mid-hills, composite soil samples at 0 cm to 20 cm depth were collected from five different land-use systems: Grassland, forest land, upland, lowland, and vegetable farms from Dhading district of Nepal in 2017. Soil samples were analyzed for soil fertility parameters: Soil pH, organic matter (OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
9
11
0
Order By: Relevance
“…There was insignificant variation in levels of K. This is in agreement with study by (Kihara et al, 2016). The variations can be attributed to land use practices, leaching and adsorption in soil (Kharal, Khanal, & Panday, 2018 Jassogne, & Merckx, 2016). The mean level of Mn in soil was 4.21± 0.61 ppm which was within the WHO acceptable limit of ≤2,000 ppm.…”
Section: Magnesiumsupporting
confidence: 86%
“…There was insignificant variation in levels of K. This is in agreement with study by (Kihara et al, 2016). The variations can be attributed to land use practices, leaching and adsorption in soil (Kharal, Khanal, & Panday, 2018 Jassogne, & Merckx, 2016). The mean level of Mn in soil was 4.21± 0.61 ppm which was within the WHO acceptable limit of ≤2,000 ppm.…”
Section: Magnesiumsupporting
confidence: 86%
“…The variations of soil pH (from highly acidic (3.70) to alkaline (9.90), EC (from 0.01 dS m -1 (non-saline) to 7.45 dS m -1 (saline)) and SOC (from 0.02 to 3.74%) were wide ( Table 2 ). In line with our findings, Kharal et al [ 55 ] reported the variations in soil pH and organic matter content in soils of Nepal under different land uses. The variations of soil pH, EC and SOC the study area is ascribed to the effects of the soil types, prevailing climatic conditions, and adoption of different crop-management practices.…”
Section: Discussionsupporting
confidence: 93%
“…These values (4.33-5.26 and 4. 74) are similar as reported by Paudel and Sah (2003) and Kharal et al(2018)in different S. robusta forests. Good S. robusta regeneration areas favor slightly acidic soils (Bhatnagar, 1965).…”
Section: Soil Fertility Status Based On Chemical Propertiessupporting
confidence: 89%